Rubber composition for dynamic sealing and method for producing the same
Patent Information
- Application Number
- CN202611436580.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-16
- Publication Date
- 2026-10-30
AI Technical Summary
[0003]针对现有技术存在的单一橡胶基体在动态密封工况下难以兼顾耐磨性、耐疲劳性与耐介质老化性的问题,本申请通过一种动态密封用橡胶组合物及其制备方法和应用,实现材料在高频动态往复运动及复杂介质环境下的长效可靠密封
[0028]有益效果:本申请提供的动态密封用橡胶组合物及其制备方法,通过氢化丁腈橡胶与聚氨酯橡胶的双基体协同设计,结合纳米增强填料、耐磨助剂与抗疲劳剂的多重功能复配,在分子链段运动与宏观力学响应之间建立了平衡机制,使材料同时具备高耐磨、高耐疲劳与优异的耐介质老化性能。配合填料预处理与分段温控混炼工艺,有效解决了纳米填料在极性双基体中的分散难题及过氧化物硫化体系的加工安全性问题。该组合物制备的密封件在高频往复运动、温湿度交变及接触润滑油、汗液等复杂介质条件下,仍能保持稳定的密封接触压力与低摩擦损耗,显著延长了动态密封系统的使用寿命与运行可靠性。
Abstract
Description
Technical Field
[0001] This invention relates to the field of special rubber materials technology, specifically to a dynamic sealing rubber composition, its preparation method, and its application. Background Technology
[0002] In dynamic sealing applications of precision machinery and intelligent equipment, seals are subjected to high-frequency reciprocating motion, frictional heat generation, and contact with complex media for extended periods. Existing sealing rubber materials typically employ a single matrix system. For example, while ordinary nitrile rubber has good oil resistance, it is prone to fatigue cracking and insufficient wear resistance under long-term dynamic stress. Silicone rubber, although possessing excellent temperature resistance and elasticity, suffers from low mechanical strength, poor wear resistance, and is prone to swelling and aging upon contact with lubricating oil or specific chemical media. Because a single rubber matrix cannot simultaneously achieve a combination of high wear resistance, high fatigue resistance, resistance to media aging, and adaptability to temperature and humidity changes, seals exhibit short service life and low reliability under complex dynamic conditions, failing to meet the requirements for high-precision, long-life dynamic sealing. Summary of the Invention
[0003] To address the problem that existing technologies with a single rubber matrix cannot simultaneously achieve wear resistance, fatigue resistance, and resistance to media aging under dynamic sealing conditions, this application provides a dynamic sealing rubber composition, its preparation method, and its application, thereby achieving long-term reliable sealing of materials under high-frequency dynamic reciprocating motion and complex media environments.
[0004] To achieve the above objectives, this application adopts the following technical solution:
[0005] A dynamic sealing rubber composition, by weight, comprises: 50-70 parts of hydrogenated nitrile rubber; 30-50 parts of polyurethane rubber; 20-40 parts of nano-reinforcing filler; 10-20 parts of wear-resistant agent; 5-10 parts of anti-fatigue agent; 3-8 parts of composite antioxidant; 2-4 parts of vulcanizing agent; and 1-3 parts of functional additive.
[0006] The above-mentioned solution combines the excellent oil and heat resistance of hydrogenated nitrile butadiene rubber with the high wear resistance and elasticity of polyurethane rubber through a dual-matrix blend system of hydrogenated nitrile butadiene rubber and polyurethane rubber, thus constructing a matrix framework that combines toughness and resilience. With the synergistic effect of nano-reinforcing fillers, wear-resistant additives and anti-fatigue agents, the mechanical retention rate and damage resistance of the material under dynamic friction interfaces are significantly improved, solving the problem of performance imbalance of traditional single matrix materials under complex working conditions.
[0007] In one embodiment, the nano-reinforcing filler includes at least one of nano-silica, carbon nanotubes, or graphene; the wear-resistant additive includes at least one of polytetrafluoroethylene micro powder, molybdenum disulfide, or ultra-high molecular weight polyethylene powder; and the anti-fatigue agent is an interface-modified additive defined based on functional effects, including at least one of silane coupling agent modified silica or liquid polybutadiene.
[0008] This embodiment improves modulus and tear strength by using high specific surface area nanoscale reinforcing fillers to construct a physical cross-linking network in the matrix; it introduces low surface energy solid lubricating wear-resistant additives to reduce the dynamic friction coefficient and frictional heat generation; and it uses modified silica or liquid polybutadiene as fatigue-resistant agents to improve the compatibility of the filler-matrix interface and absorb dynamic stress concentration, thereby delaying the initiation and propagation of fatigue cracks from a microstructural perspective. It should be noted that the silane coupling agent-modified silica and liquid polybutadiene mentioned above are preferred examples of fatigue-resistant agents, not an exhaustive list; those skilled in the art, guided by the functional definition of this application, can choose other substances with equivalent interface modification and stress dissipation functions as substitutes, as long as they fall within the functional limitations of fatigue-resistant agents, they can achieve the corresponding technical effects.
[0009] In one embodiment, the composite antioxidant is a combination system of antioxidant RD and antioxidant MB; the vulcanizing agent is peroxide vulcanizing agent BIPB or 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane (bis25); the functional additives include at least one of hydrolysis resistant agent, antistatic agent or thermally conductive filler.
[0010] This implementation utilizes the synergistic effect of antioxidants RD and MB to provide dual protection against thermo-oxidative aging and metal ion catalytic aging, respectively; it selects peroxide vulcanizing agents to form stable carbon-carbon crosslinks, improving heat resistance to compression set; and it introduces functional additives such as hydrolysis resistance, antistatic properties, or thermal conductivity according to working conditions to further enhance the material's adaptability to specific environmental factors such as humidity, static electricity accumulation, or heat accumulation.
[0011] As one embodiment, the rubber composition for dynamic sealing meets the following performance indicators: hardness of Shore A 60-75; tensile strength ≥12MPa; elongation at break ≥300%; compression set ≤20% under 150℃×24h conditions.
[0012] This implementation method ensures that the material has appropriate sealing contact pressure, sufficient structural strength, and excellent high-temperature deformation recovery capability during actual assembly and operation by quantifying key physical and mechanical performance parameters, thus providing a clear performance benchmark for the reliability of dynamic seals.
[0013] Furthermore, this application also provides a method for preparing a dynamic sealing rubber composition as described above, comprising the following steps:
[0014] Pretreatment: The nano-reinforced filler and a portion of the anti-fatigue agent are stirred and pretreated to obtain a pretreated filler system;
[0015] First stage of mixing: The hydrogenated nitrile rubber and the polyurethane rubber are plasticized, and then the pretreated filler system, the wear-resistant additive and the composite antioxidant are added and mixed. The glue is discharged to obtain the premixed rubber.
[0016] Two-stage mixing: After cooling the premixed rubber, the vulcanizing agent, the functional additive and the remaining anti-fatigue agent are added and mixed to obtain the dynamic sealing rubber composition.
[0017] The above preparation method effectively inhibits the agglomeration of nanoparticles in subsequent mixing by using a filler pretreatment step to pre-coat and disperse the nanofillers with an anti-fatigue agent. The segmented mixing process completes matrix plasticization and filler dispersion in the high-temperature section and adds vulcanizing agent and sensitive additives in the low-temperature section, which not only ensures the uniform mixing of each component, but also avoids the early scorching of peroxide vulcanizing agent under high-temperature shear, thus ensuring processing safety and the performance stability of the final product.
[0018] In one implementation, the temperature of the first stage of mixing is controlled at 110-120℃; the temperature of the second stage of mixing is controlled at 80-95℃.
[0019] This implementation precisely defines the temperature window for the two-stage mixing process. The first-stage mixing temperature is sufficient to fully soften and flow the dual matrix to promote filler wetting and dispersion, while remaining below the filler structuring failure temperature. The second-stage mixing temperature is controlled below the vulcanizing agent activation temperature to prevent pre-crosslinking during the mixing process, thus ensuring the processing rheological properties of the rubber compound and the integrity of the network structure after vulcanization.
[0020] In one embodiment, the plasticizing time is 60-80 seconds; the mixing time after adding the pretreated filler system, the wear-resistant additive and the composite antioxidant in the first stage of mixing is 90-120 seconds; and the mixing time of the second stage of mixing is 60-90 seconds.
[0021] This implementation method optimizes the mixing time at each stage, shortens the high-temperature shearing time while ensuring uniform dispersion, reduces the risk of thermomechanical degradation of polymer chains, and ensures rapid and uniform distribution of vulcanizing agents and functional additives in the low-temperature range, thereby improving production efficiency and batch stability.
[0022] In one embodiment, during the pretreatment, the nano-reinforced filler and a portion of the anti-fatigue agent are fully dispersed by high-speed stirring; during the two-stage mixing, the cooled premixed rubber is re-input into the internal mixer, and then mixed after adding the vulcanizing agent, the functional additives and the remaining anti-fatigue agent.
[0023] This implementation method further refines the operational details, emphasizing the high-speed dispersion kinetic energy input in the pretreatment stage to ensure the deagglomeration effect of the nanofiller, and the operational specifications for feeding the premixed rubber after cooling in the two-stage mixing process. From the process execution level, it eliminates the risk of scorching and poor dispersion defects caused by local overheating.
[0024] In addition, this application also provides a dynamic seal, the material of which comprises a dynamic sealing rubber composition as described in any of the preceding claims.
[0025] This embodiment processes the aforementioned rubber composition with dual matrix synergistic reinforcement and multifunctional additive compounding characteristics into a solid sealing product, so that the material inherits the characteristics of highly dispersed nanofillers, strong interfacial bonding and stable cross-linking network in the microstructure, thereby exhibiting excellent comprehensive sealing ability in macroscopic performance.
[0026] As one implementation method, the aforementioned dynamic seal is used for joint sealing in AI humanoid robots.
[0027] This implementation addresses the stringent sealing requirements of AI humanoid robot joints under conditions of high-frequency reciprocating motion, complex media contact, and precise force control. By leveraging the material advantages of the aforementioned dynamic seals, it ensures dimensional stability in a lubricating oil environment while providing the sealing interface with an extremely low coefficient of friction and excellent wear resistance. This effectively solves the technical challenges of insufficient wear resistance, poor media resistance, and easy fatigue failure of traditional seals under such conditions.
[0028] Beneficial Effects: The dynamic sealing rubber composition and its preparation method provided in this application, through the synergistic design of a dual matrix of hydrogenated nitrile butadiene rubber and polyurethane rubber, combined with the multifunctional compounding of nano-reinforcing fillers, wear-resistant additives, and anti-fatigue agents, establish a balance mechanism between molecular chain segment movement and macroscopic mechanical response, enabling the material to simultaneously possess high wear resistance, high fatigue resistance, and excellent resistance to media aging. Combined with filler pretreatment and segmented temperature-controlled mixing processes, the dispersion problem of nano-fillers in polar dual matrices and the processing safety issues of peroxide vulcanization systems are effectively solved. The seals prepared from this composition can maintain stable sealing contact pressure and low friction loss even under conditions of high-frequency reciprocating motion, alternating temperature and humidity, and contact with complex media such as lubricating oil and sweat, significantly extending the service life and operational reliability of dynamic sealing systems. Detailed Implementation
[0029] To make the objectives and advantages of this invention clearer, the invention will be specifically described below with reference to embodiments. It should be understood that the following text is merely used to describe one or more specific embodiments of the invention and does not strictly limit the scope of protection specifically claimed by the invention.
[0030] Example 1: This example provides a basic formulation framework for a rubber composition for dynamic sealing. By weight, the components of this rubber composition for dynamic sealing include: 50-70 parts hydrogenated nitrile rubber; 30-50 parts polyurethane rubber; 20-40 parts nano-reinforcing filler; 10-20 parts abrasion-resistant agent; 5-10 parts fatigue-resistant agent; 3-8 parts composite antioxidant; 2-4 parts vulcanizing agent; and 1-3 parts functional additives.
[0031] Specifically, the above formulation constructs a matrix framework that combines high toughness and resilience through a dual-matrix blend system of hydrogenated nitrile butadiene rubber (NBR) and polyurethane rubber. The high molecular chain saturation of NBR imparts excellent oil resistance, heat aging resistance, and mechanical strength to the material, providing stable structural support for seals operating in media such as lubricating oils for extended periods. Polyurethane rubber, on the other hand, possesses extremely high wear resistance, tear strength, and low-temperature flexibility. Its polar groups and soft segments effectively reduce the dynamic friction coefficient and adapt to high-frequency reciprocating deformation. When the two are blended within the aforementioned ratio range, NBR acts as a continuous or co-continuous phase, providing a barrier against the medium, while polyurethane rubber acts as a dispersed phase or interpenetrating network node, providing elastic compensation and wear protection. This solves the performance imbalance problems of single NBR easily fatigue cracking under long-term dynamic stress and single polyurethane rubber's insufficient oil and hydrolysis resistance.
[0032] Based on this dual-matrix framework, nano-reinforcing fillers, wear-resistant additives, and fatigue-resistant agents synergistically construct a "reinforcement-lubrication-stress dissipation" functional network at the microscopic level. Nano-reinforcing fillers, with their high specific surface area, can form dense polymer-filler interaction zones within the matrix, acting as physical cross-linking points and significantly improving the material's modulus, hardness, and extrusion resistance. Wear-resistant additives, typically low-surface-energy solid lubricating particles, migrate to the sealing interface during dynamic friction to form a transfer film, transforming the dry friction between the rubber and its mating parts into low-shear-resistance interlaminar slip, drastically reducing frictional heat generation and wear rate. Fatigue-resistant agents, introduced through chemical modification or flexible segments, improve the interfacial compatibility between the inorganic filler and the organic dual matrix, absorbing and dissipating dynamic stress concentration energy at microscopic defects, thus delaying the initiation and propagation of fatigue cracks. This combination of three additives is not a simple additive layer, but a systematic defensive design targeting the three main failure modes—mechanical damage, frictional wear, and fatigue failure—under dynamic sealing conditions.
[0033] In addition, composite antioxidants are used to resist thermo-oxidative aging and metal ion catalytic aging, ensuring the long-term stability of materials under high temperature and complex environments; vulcanizing agents are used to build a stable three-dimensional cross-linked network, ensuring that the materials have suitable compression set performance and high-temperature dimensional stability; functional additives, according to the specific application scenario requirements, endow the materials with additional functions such as hydrolysis resistance, antistatic properties or thermal conductivity, further improving their adaptability to specific environmental factors such as temperature and humidity changes, static electricity accumulation or heat accumulation.
[0034] It should be noted that the term "anti-fatigue agent" in this application refers to a functional classification based on functional effects. Specifically, it refers to functional additives that can delay the initiation and propagation of fatigue damage under repeated dynamic stress by improving the interfacial compatibility between fillers and the rubber matrix, enhancing interfacial stress transfer efficiency, and absorbing and dissipating dynamic stress concentration energy at micro-defects. Specifically, silane coupling agent-modified silica significantly improves the interfacial bonding strength between inorganic fillers and the organic matrix through chemical bonding or strong hydrogen bonding between the silane coupling agent on its surface and the rubber molecular chains, reducing interfacial debonding and the formation of microvoids during dynamic deformation. Liquid polybutadiene, with its flexible segments, penetrates into the matrix network, providing additional energy dissipation channels in stress concentration areas. Although their mechanisms of action differ from traditional chemical antioxidants, both achieve macroscopic fatigue resistance by improving the micro-interfacial structure; therefore, they are uniformly classified as anti-fatigue agents in this application. It should be understood that the silane coupling agent modified silica and liquid polybutadiene mentioned above are only preferred examples of anti-fatigue agents, and not an exhaustive list. Under the guidance of the functional definition in this application, those skilled in the art can choose other substances with equivalent interface modification and stress dissipation functions to replace them, as long as they fall within the functional limits of anti-fatigue agents, they can achieve the corresponding technical effects.
[0035] It should be understood that the eight components and their wide range of proportions shown in this embodiment constitute the general basic framework of rubber compositions for dynamic sealing. This framework is designed to solve the sealing reliability problems of precision machinery and intelligent equipment under conditions of high-frequency reciprocating motion, frictional heat generation, and complex media contact. Its technical principles are universal and not limited to specific equipment models or application carriers. As long as it is within the technical scenario of dynamic sealing, whether applied to humanoid robot joints, industrial hydraulic cylinders, or automotive transmission systems, this basic framework can be used to adapt to specific working conditions by adjusting the types and proportions of each component. Subsequent embodiments will further demonstrate preferred material selections and performance verification data based on this framework.
[0036] Example 2: Based on the basic formulation framework of the dynamic sealing rubber composition provided in Example 1, this example further specifies the types of core additives and auxiliary additive systems to verify the supporting role of the preferred components in achieving key performance indicators. Specifically, the nano-reinforcing filler includes at least one of nano-silica, carbon nanotubes, or graphene; the wear-resistant additive includes at least one of polytetrafluoroethylene micropowder, molybdenum disulfide, or ultra-high molecular weight polyethylene powder; the fatigue-resistant agent is an interface-modified additive defined based on functional effects, including at least one of silane coupling agent modified silica or liquid polybutadiene. Meanwhile, the composite antioxidant is a combined system of antioxidant RD and antioxidant MB; the vulcanizing agent is peroxide vulcanizing agent BIPB or bis25; the functional additive includes at least one of hydrolysis-resistant agent, antistatic agent, or thermally conductive filler.
[0037] To more clearly illustrate the selection logic and technical effects of the above-mentioned preferred components, three specific formulation examples are provided below for detailed explanation. Table 1 shows the specific formulation composition of Examples 1 to 3. The proportions of each group are within the wide range determined in Example 1, but the emphasis is different.
[0038] Table 1 Formulation Table for Examples 1-3
[0039] Ingredients (number of servings) Example 1 Example 2 Example 3 Hydrogenated nitrile rubber 60 55 65 polyurethane rubber 40 45 35 Nano silica 30 25 35 polytetrafluoroethylene micro powder 15 12 18 Anti-fatigue agent (silane-modified silica) 8 6 10 Anti-aging agent RD+MB 5 4 6 BIPB vulcanizing agent 3 2.5 3.5 Hydrolysis resistant agent 2 1.5 2.5
[0040] Specifically, Example 1 serves as a balanced baseline formulation with moderate values for each component, aiming to verify the overall performance balance of the basic structure. Example 2 appropriately increases the proportion of polyurethane rubber and adjusts the proportions of the remaining components accordingly, focusing on further enhancing the material's elastic compensation capability and dynamic wear resistance, making it suitable for more demanding scenarios involving high-frequency reciprocating friction. The amount of nano-silica and anti-fatigue agent used is slightly reduced compared to Example 1, aiming to avoid excessive filler content leading to excessive hardness of the rubber compound and weakening the flexibility gain brought by the increased proportion of polyurethane rubber. Example 3 increases the amount of hydrogenated nitrile rubber, polytetrafluoroethylene micro powder, and anti-fatigue agent, focusing on strengthening resistance to media swelling and long-term anti-fatigue performance to meet the long-term sealing requirements of contact with complex media such as lubricating oil or sweat. It should be understood that the nano-silica, polytetrafluoroethylene micro powder, silane-modified silica, etc. shown in Table 1 are only exemplary choices. In other embodiments, carbon nanotubes, molybdenum disulfide, liquid polybutadiene, etc., can also be used as substitutes according to actual working conditions. As long as they fall within the range of the aforementioned preferred components, the corresponding technical effects can be achieved.
[0041] The key physical and mechanical properties of the rubber compositions prepared by the above three formulations are shown in Table 2. The dynamic sealing rubber composition meets the following performance indicators: hardness Shore A 60-75; tensile strength ≥12MPa; elongation at break ≥300%; compression set ≤20% under 150℃×24h conditions.
[0042] Table 2 Performance test data for Examples 1-3
[0043] Physical property indicators Example 1 Example 2 Example 3 Hardness (Shore A) 66 64 67 Tensile strength (MPa) 16.8 15.2 17.5 Elongation at break (%) 380 365 395 Compression set (%) 12 14 11 Reciprocating motion life (ten thousand cycles) 850 820 880 Percentage change in volume of sweat (%) 3.2 4.1 2.8 Tensile strength retention rate after heat aging (%) 88 86 90
[0044] As can be seen from the data in Table 2, all performance indicators of Examples 1 to 3 consistently fall within the preset performance window, fully demonstrating the rationality and reliability of the aforementioned preferred component types and proportions. Specifically, the hardness is controlled between Shore A 64 and 67, ensuring both ease of assembly of the seals and providing sufficient contact sealing pressure; the tensile strength exceeds 15 MPa, far exceeding the lower limit requirement of 12 MPa, ensuring the structural integrity of the material under high-pressure dynamic conditions; the elongation at break reaches over 365%, endowing the material with excellent flexibility and deformation following ability; the high-temperature compression set at 150℃ for 24 hours is as low as 11%-14%, indicating that the material can still maintain good resilience under long-term high-temperature compression, effectively preventing seal failure.
[0045] More importantly, the aforementioned superior performance is not a simple superposition of the components, but rather stems from the microscopic synergistic effect brought about by the selection of specific substances. For example, using silane coupling agent-modified silica as an anti-fatigue agent, compared to unmodified conventional silica, the silane coupling agent on its surface can chemically bond or strongly hydrogen bond with the polar groups on the molecular chains of hydrogenated nitrile rubber and polyurethane rubber, significantly enhancing the interfacial bonding force between the inorganic filler and the organic dual matrix. This strong interfacial effect not only improves stress transfer efficiency and greatly increases tensile strength, but also effectively inhibits the debonding and microvoid formation of the filler-matrix interface during dynamic deformation, thereby delaying the initiation of fatigue cracks. This is the fundamental reason why the reciprocating motion life of Examples 1-3 all exceeded 8 million cycles. Furthermore, using a system combining antioxidants RD and MB, utilizing RD's excellent protection against thermo-oxidative aging and MB's specific inhibition of metal ion catalytic aging, a dual protective barrier is constructed, enabling the material to retain a tensile strength of over 86% after hot air aging at 125℃ for 72 hours. In addition, as a solid lubricating wear-resistant additive, polytetrafluoroethylene micro powder forms a low shear strength transfer film at the sealing interface during dynamic friction, transforming the direct dry friction between the rubber and the mating parts into interlayer slip, which greatly reduces the coefficient of friction and frictional heat generation. This not only directly contributes to high wear resistance, but also indirectly reduces the risk of thermal aging degradation caused by temperature rise, demonstrating the synergistic effect of wear resistance and aging resistance.
[0046] Example 4: This example provides a method for preparing the dynamic sealing rubber composition described in Example 1 above. This method, through a specific feeding sequence and segmented mixing strategy, aims to solve the technical contradictions of the difficulty in uniformly dispersing nanofillers in a polar bimatrix and the tendency of the peroxide vulcanization system to undergo early scorching under high-temperature processing, ensuring batch-to-batch stability of the final product performance. Specifically, the preparation method includes the following steps:
[0047] Step S100, Pretreatment: The nano-reinforced filler and a portion of the anti-fatigue agent are stirred and pretreated to obtain a pretreated filler system.
[0048] Specifically, this step is not a simple physical mixing process, but rather a process of in-situ surface modification and deagglomeration of the nano-reinforced filler using an anti-fatigue agent. Because nano-reinforced fillers have extremely high specific surface area and surface energy, direct input into a mixer easily leads to the formation of hard, difficult-to-open agglomerates due to van der Waals forces, resulting in stress concentration points within the material. In this embodiment, a portion of the anti-fatigue agent (such as silane coupling agent-modified silica or liquid polybutadiene) is pre-mixed with the nano-filler at high speed, allowing the anti-fatigue agent molecules to preferentially adsorb and coat the nanoparticle surface. This reduces the surface energy of the particles, effectively preventing secondary agglomeration. Furthermore, the active functional groups or flexible segments in the anti-fatigue agent are pre-anchored to the filler surface, laying the microstructural foundation for establishing a strong interfacial bond between the filler and the hydrogenated nitrile rubber and polyurethane rubber matrix during subsequent mixing. This pretreatment mechanism significantly improves the dispersion efficiency and interfacial compatibility of the filler in the dual matrix, making it a crucial pre-treatment step for achieving high wear resistance and high fatigue resistance.
[0049] Step S200, first stage of mixing: The hydrogenated nitrile rubber and polyurethane rubber are plasticized, and then the pre-treatment filler system, wear-resistant additives and composite antioxidants are added and mixed. The premixed rubber is obtained by debinding.
[0050] Specifically, the core function of the first-stage mixing process is to construct a uniform filler-rubber compound network, belonging to the "high-temperature, high-dispersion" stage. In this stage, the dual-matrix rubber is fully plasticized and its viscosity decreases under mechanical shear, providing a suitable rheological environment for the wetting and dispersion of the filler. The addition of pretreated filler systems, abrasion-resistant additives, and composite antioxidants at this stage enables uniform microscale distribution through the higher mixing temperature and strong shear forces. It is crucial to note that the addition of vulcanizing agents is strictly prohibited at this stage. Peroxide vulcanizing agents are heat-sensitive; if added during the high-temperature, high-shear environment of the first-stage mixing process, they can easily trigger early cross-linking reactions (i.e., scorching), leading to loss of processing fluidity and even rendering the rubber compound unusable. Therefore, the process design of the first-stage mixing process ensures dispersion quality while mitigating the risk of thermal damage from vulcanizing agents at the source.
[0051] Step S300, two-stage mixing: After cooling the premixed rubber, add vulcanizing agent, functional additives and remaining anti-fatigue agent for mixing, and sheet out to obtain a rubber composition for dynamic sealing.
[0052] Specifically, the core function of the two-stage mixing process is to safely introduce the crosslinking system and complete the final homogenization, which belongs to the "low-temperature anti-scorching" stage. Before entering the two-stage mixing process, the premixed rubber must undergo sufficient cooling to eliminate the internal heat accumulated in the first-stage mixing, ensuring that the initial mixing temperature is below the activation threshold of the vulcanizing agent. Adding the vulcanizing agent, functional additives, and remaining anti-fatigue agent under these low-temperature conditions ensures the rapid and uniform distribution of these heat-sensitive or functional components in the rubber compound, while completely eliminating the risk of scorching. The addition of the remaining anti-fatigue agent at this stage can further adjust the crosslinking density of the system or supplement the interface modification effect, avoiding insufficient interface control ability in the later stages due to the depletion of all anti-fatigue agent in the pretreatment stage. Through this segmented temperature control and differentiated feeding strategy, the preparation method provided in this embodiment ensures the high dispersion of nanofillers while achieving safe processing of the peroxide vulcanization system, providing a reliable process guarantee for obtaining a stable and defect-free dynamic sealing rubber composition. It should be understood that the above process framework is universally applicable. Specific temperature settings, mixing time, and rotation speed parameters can be adjusted within a certain range according to the actual equipment model and production scale. As long as the core logic of "pretreatment coating - high-temperature dispersion - low-temperature anti-scorching" is followed, the corresponding technical effects can be achieved. The dynamic sealing rubber composition prepared by the method described in this embodiment has been verified by performance testing. Its hardness, tensile strength, elongation at break, and compression set, among other performance indicators, consistently meet the performance requirements listed in Table 2 of the aforementioned Example 2. This fully demonstrates that the synergistic cooperation between the above-mentioned segmented temperature-controlled mixing process and the pretreatment step can ensure that the final product achieves the expected comprehensive performance level.
[0053] Example 5: Building upon the basic process framework provided in Example 4, this example further specifies the key process parameter windows and operational details to construct a safe processing window that ensures both high dispersion of the nanofiller and effective prevention of scorching of the peroxide vulcanizing system. Specifically, the temperature of the first-stage mixing is controlled at 110-120℃; the temperature of the second-stage mixing is controlled at 80-95℃. This temperature window setting is based on a comprehensive consideration of the rheological properties of the hydrogenated nitrile rubber and polyurethane rubber dual matrix and the thermal stability of the peroxide vulcanizing agent. During the mixing stage, a temperature range of 110-120℃ allows the bimatrix rubber to soften sufficiently and reach a suitable viscosity matching state, providing the necessary thermodynamic conditions and shear transfer medium for the wetting and dispersion of nano-reinforced fillers. If the temperature is below 110℃, the rubber viscosity is too high, resulting in intense shear heat generation and difficulty in breaking up the filler agglomerates, which can easily lead to poor dispersion and surface defects. If the temperature is above 120℃, although the fluidity increases, it will significantly increase the risk of premature activation of the peroxide vulcanizing agent (even if no vulcanizing agent is added at this stage, the residual heat accumulation will affect subsequent processes), and may also cause thermal degradation of the soft segments of polyurethane rubber or aging of hydrogenated nitrile rubber. During the two-stage mixing stage, the temperature range of 80-95℃ was strictly controlled below the half-life temperature of the peroxide vulcanizing agent used (such as BIPB or Bi-25), ensuring that the vulcanizing agent, functional additives, and remaining anti-fatigue agents could achieve molecular-level uniform distribution without chemical cross-linking. If the temperature exceeds 95℃, the vulcanizing agent is prone to early cross-linking reaction under the action of mixing shear heat, leading to the formation of cooked rubber particles or even the scrapping of the entire batch. If the temperature is below 80℃, the rubber compound lacks fluidity, making it difficult to disperse trace components evenly in a short time, affecting the performance consistency of the final product. The preparation processes of Examples 1 to 3 mentioned above all strictly fell within this temperature window, thus obtaining stable physical and mechanical properties.
[0054] Furthermore, the time parameters of each mixing stage are closely coupled with the temperature window, jointly determining the microstructure and processing safety of the material. The plasticizing time is 60-80 seconds; the mixing time after adding the pretreated filler system, wear-resistant additives, and composite antioxidants in the first-stage mixing is 90-120 seconds; and the mixing time for the second-stage mixing is 60-90 seconds. Specifically, the plasticizing time is controlled at 60-80 seconds to allow the dual-matrix rubber to quickly obtain suitable plasticity and roll-wrapping properties, while avoiding irreversible breakage and degradation of the polymer backbone due to excessive mechanical shearing, thus preserving the material's original high strength and fatigue resistance potential. The first-stage mixing time is set at 90-120 seconds, which is the optimal duration determined based on the deagglomeration kinetics of nanofillers. This is sufficient for the pretreated filler system to complete the transformation from micron-scale aggregates to nano-scale dispersed phases under the coupling effect of shear and thermal fields, and to form a good interfacial bond with the rubber matrix; too short a time results in insufficient dispersion, while too long a time increases ineffective energy consumption and the risk of heat accumulation. The second-stage mixing time is controlled at 60-90 seconds. Considering that the rubber compound already has good plasticity at this stage and only a small amount of additives need to be mixed, the shorter mixing time combined with low temperature conditions not only ensures the macroscopic uniformity and microscopic dispersion of vulcanizing agents and functional additives, but also minimizes the time that the rubber compound is under thermal stress, further reducing the probability of scorching and improving production efficiency.
[0055] Furthermore, to ensure the effective execution of the aforementioned process parameters and the precise control of the microstructure, this embodiment also standardizes and defines key operational steps. In the pretreatment stage, high-speed stirring ensures thorough dispersion of the nano-reinforced filler and some of the fatigue-resistant agent. In the second-stage mixing stage, the cooled premixed rubber is re-introduced into the internal mixer, and mixing is performed after adding the vulcanizing agent, functional additives, and the remaining fatigue-resistant agent. Here, "high-speed stirring" does not refer to general mixing, but specifically to a dispersion process that provides sufficient shear energy to overcome the van der Waals forces between nanoparticles. The strong turbulence and shear force generated by high-speed stirring force the fatigue-resistant agent molecules to rapidly penetrate and adsorb onto the surface of the nanofiller, forming a uniform organic coating layer. This in-situ modification effect cannot be replaced by subsequent low-speed mixing and directly determines the upper limit of filler dispersion and interfacial bonding strength in the matrix. The emphasis on re-introducing after cooling in the second-stage mixing stage is to completely cut off the thermal history accumulated during the first-stage mixing. After the premixed rubber is discharged, it must undergo sufficient cooling and resting to allow its internal temperature to drop to room temperature or close to the starting temperature of the second-stage mixing before being re-introduced into the internal mixer. This operating procedure eliminates the risk of localized overheating caused by the premixed tape entering the machine at a low temperature, ensures the controllability of the initial temperature of the second-stage mixing and the environmental safety when adding the vulcanizing agent, and is a key process discipline to ensure batch-to-batch performance stability and avoid hidden scorching defects. It should be understood that the above parameter range and operating details constitute an interrelated process control system. In actual production, adaptive fine-tuning can be made within this range according to factors such as equipment capacity, rotor configuration and ambient temperature. As long as the core principles of "high-temperature dispersion to prevent scorching, low-temperature mixing to ensure uniformity, pretreatment coating to strengthen the interface, and cooling and re-injection to break the heat history" are followed, the expected technical effects of this application can be achieved.
[0056] Example 6: This example provides a dynamic seal, the material of which comprises the dynamic sealing rubber composition described in any one of Examples 1 to 5 above. Specifically, the dynamic seal is a solid product processed by molding processes such as compression molding, extrusion molding, or injection molding of the compound rubber obtained in the above examples. Its specific form can be adapted according to the geometry and functional requirements of the sealing interface, for example, it can be an O-ring, a rotary shaft oil seal, a shaped dust cover, or an end face sealing gasket. Since the material of this seal directly adopts the aforementioned rubber composition with dual matrix synergistic reinforcement and multifunctional additive compounding characteristics, it inherits the characteristics of highly dispersed nanofillers, strong interfacial bonding force, and stable cross-linked network in its microstructure, thus exhibiting excellent comprehensive sealing ability in macroscopic performance. It should be understood that although this example is described using a specific seal form as an example, in other embodiments, any elastic sealing product made of this dynamic sealing rubber composition for preventing fluid leakage or isolating external contaminants falls within the protection scope of this application.
[0057] As a preferred application scenario, the aforementioned dynamic seals are used for joint sealing in AI humanoid robots. In the actual operation of AI humanoid robots, joints and drive units are core components for performing high-frequency reciprocating motion and precise force control. Their internal seals are subjected to extremely harsh dynamic conditions for extended periods: on the one hand, robot walking and grasping actions require frequent start-stop and reversal of the joint motors, requiring the sealing lips to withstand several or even dozens of friction cycles per second, accompanied by significant frictional heat generation; on the other hand, the seals not only come into contact with internal lubricating grease or gear oil but may also be exposed to complex media such as moisture, dust, and even human sweat in the external environment. Traditional single-matrix rubber seals often fail rapidly under such conditions due to insufficient wear resistance or swelling and hardening due to poor media resistance, leading to seal leakage or movement stagnation. The dynamic seal provided in this embodiment, through the synergistic effect of hydrogenated nitrile rubber and polyurethane rubber in the material, not only ensures dimensional stability in a lubricating oil environment, but also endows the sealing interface with an extremely low coefficient of friction and excellent wear resistance. At the same time, the introduction of nano-reinforcing fillers and anti-fatigue agents significantly improves the material's ability to resist high-frequency dynamic stress damage and effectively delays the initiation of fatigue cracks.
[0058] To more intuitively demonstrate the technical advantages of this dynamic seal in AI humanoid robot applications, the performance test data in Table 2 above are used for illustration. In the durability test simulating the high-frequency reciprocating motion of robot joints, the seals prepared using the formulations of Examples 1 to 3 all achieved a reciprocating motion life of over 8.2 million cycles, with the highest reaching 8.8 million cycles, far exceeding the conventional level of 3-5 million cycles for general industrial robot seals. This means that maintenance downtime due to seal failure can be significantly reduced throughout the robot's entire lifespan. Regarding media resistance, for environments where robots may come into contact with human sweat, the volume change rate of this seal after sweat immersion is only 2.8%-4.1%, far lower than the swelling level of over 7.5% for a single matrix material in the comparative examples. This ensures that the seal can maintain precise dimensional tolerances and appropriate contact pressure after absorbing liquid, avoiding the risk of increased friction due to excessive swelling or leakage due to shrinkage. Furthermore, the seal exhibits a low compression set of only 11%-14% at 150°C, demonstrating its ability to maintain a durable, resilient sealing force even under temperature rises caused by motor heat. In summary, the dynamic seal provided in this embodiment, through deep integration of materials and structure, precisely solves the sealing reliability problem for AI humanoid robots under complex dynamic operating conditions. It is also suitable for sealing systems in other precision electromechanical equipment with similarly high requirements for wear resistance, fatigue resistance, and media resistance.
[0059] Comparative Examples 1-2: To further verify the synergistic effect among the components in the dynamic sealing rubber composition of this application and its necessity for achieving the expected technical effect, the following comparative examples were set up for negative verification. These comparative examples, by intentionally omitting or replacing key components, simulated common single-matrix or simplified formulation systems in the prior art, aiming to demonstrate from the opposite perspective the integrity and irreplaceability of the formulation architecture of this application.
[0060] Comparative Example 1 used a fully hydrogenated nitrile butadiene rubber system, i.e., without polyurethane rubber, using only hydrogenated nitrile butadiene rubber as the matrix, with the remaining components and preparation process being the same as in Example 1. This comparative example aimed to investigate the impact of the absence of polyurethane rubber on the overall performance of the material. The test results showed that the rubber composition prepared in Comparative Example 1 had a Shore A hardness of 68, a tensile strength of 14.1 MPa, an elongation at break of 320%, a compression set of up to 22% under 150℃×24h conditions, a reciprocating motion life of only 4.8 million cycles, a volume change rate of 7.5% in sweat, and a tensile strength retention rate of 78% after heat aging. Specific analysis revealed that although the fully hydrogenated nitrile butadiene rubber system retained good oil resistance and heat resistance, due to the lack of strong intermolecular forces provided by the highly polar urethane groups in the polyurethane rubber molecular chain and the high resilience imparted by the soft segments, the material could not form an effective elastic compensation and wear-resistant protective layer at the dynamic friction interface. This directly leads to an increased coefficient of friction and intensified heat generation during high-frequency reciprocating motion, resulting in the rapid initiation and propagation of fatigue cracks. Consequently, the reciprocating motion life drops sharply to 4.8 million cycles compared to Example 1, far below the excellent level of over 8 million cycles. Simultaneously, due to the lack of polyurethane rubber to regulate the flexibility of the cross-linked network, the stress relaxation rate of the material under long-term high-temperature compression accelerates, and the compression set deteriorates to 22%, exceeding the 20% performance limit. This means that the seal is highly susceptible to leakage under high-temperature conditions due to insufficient resilience. Furthermore, the sweat volume change rate rises to 7.5%, indicating that the dimensional stability of a single hydrogenated nitrile rubber matrix is inferior to that of a dual-matrix blend system when dealing with complex hydrophilic media.
[0061] Comparative Example 2, based on Example 1, completely omitted the nano-reinforcing filler and wear-resistant additives, while keeping the remaining components and preparation process unchanged. This comparative example aimed to investigate the impact of the absence of these two key functional additives on the material's mechanical properties and resistance to media. Test data showed that the rubber composition obtained in Comparative Example 2 had a hardness reduced to Shore A 62, a tensile strength of only 10.3 MPa, an elongation at break of 290%, a compression set as high as 28%, a reciprocating motion life sharply reduced to 3.1 million cycles, a volume change rate in sweat soaring to 9.2%, and a tensile strength retention rate of only 72% after heat aging. From a microscopic mechanism perspective, the absence of the nano-reinforcing filler resulted in the loss of high-density physical cross-linking points and stress transmission media within the rubber matrix, leading to a significant decline in material modulus and strength. The tensile strength fell below the critical threshold of 12 MPa, making it unable to withstand the mechanical loads of dynamic sealing assembly and operation. Meanwhile, the absence of wear-resistant additives results in a lack of a low-shear-strength solid lubricant transfer film at the sealing interface. The rubber and mating parts are in a state of high-resistance dry friction, which not only accelerates surface wear but also induces a vicious cycle of thermo-oxidative aging and mechanical degradation due to intense frictional heat generation, leading to a reciprocating motion life of only 3.1 million cycles. More seriously, due to the lack of nanofiller filling effect on the polymer's free volume and the lack of wear-resistant additives contributing to surface density, media molecules can more easily penetrate into the rubber network, resulting in a sweat swelling rate as high as 9.2%. This excessive volume expansion directly alters the geometry and contact pressure distribution of the seal, easily causing jamming or seal failure in practical applications.
[0062] The analytical results of Comparative Examples 1 and 2 clearly demonstrate that the dynamic sealing rubber composition provided in this application is not a simple superposition of components, but a highly synergistic organic whole. The dual-matrix blending of hydrogenated nitrile butadiene rubber and polyurethane rubber resolves the inherent contradiction between oil resistance and high elasticity and wear resistance in a single matrix; the combination of nano-reinforcing fillers and wear-resistant additives constructs a defense network against dynamic damage from both microscopic reinforcement and interfacial lubrication dimensions. The absence of any single component would lead to the collapse of the material performance system, failing to meet the stringent sealing requirements of precision equipment such as AI humanoid robots under high-frequency reciprocating, complex media, and long-life operating conditions. This negative verification result strongly supports the inventiveness and industrial practical value of the technical solution in this application, while also defining the boundaries of the necessary technical features within the scope of protection of this application. It should be understood that the above comparative examples are only used to illustrate the superiority and necessity of the technical solution in this application and do not constitute a limitation on the scope of protection of this application.
[0063] The above description is merely a specific embodiment of this application, but the scope of protection of this application is not limited thereto. Any variations, substitutions, or equivalent alternatives that can be easily conceived by those skilled in the art within the scope of the technology disclosed in this application, based on the core technical concepts such as the dual-matrix synergistic reinforcement mechanism, filler pretreatment dispersion strategy, and segmented temperature-controlled mixing process disclosed in this application, such as adjusting the specific ratio of hydrogenated nitrile rubber and polyurethane rubber, selecting other nano-reinforced fillers or wear-resistant additives with equivalent functions, making adaptive process fine-tuning within the stated temperature and time window, or applying this dynamic sealing rubber composition to dynamic sealing scenarios of other precision electromechanical equipment besides AI humanoid robots, should all be covered within the scope of protection of this application. Therefore, the scope of protection of this application should be determined by the scope of the claims.
Claims
1. A rubber composition for dynamic sealing, characterized in that, The composition of the dynamic sealing rubber composition comprises, by weight, 50-70 parts of hydrogenated nitrile rubber; 30-50 parts of polyurethane rubber; 20-40 parts of nano-reinforcing filler; 10-20 parts of wear-resistant agent; 5-10 parts of anti-fatigue agent; 3-8 parts of composite antioxidant; 2-4 parts of vulcanizing agent; and 1-3 parts of functional additive.
2. The rubber composition for dynamic sealing according to claim 1, characterized in that, The nano-reinforced filler includes at least one of nano-silica, carbon nanotubes, or graphene; The wear-resistant additive includes at least one of polytetrafluoroethylene micro powder, molybdenum disulfide, or ultra-high molecular weight polyethylene powder. The fatigue-resistant agent includes at least one of silane coupling agent modified silica or liquid polybutadiene.
3. The rubber composition for dynamic sealing according to claim 2, characterized in that, The composite antioxidant is a combination system of antioxidant RD and antioxidant MB; the vulcanizing agent is peroxide vulcanizing agent BIPB or 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane; the functional additives include at least one of hydrolysis resistant agent, antistatic agent or thermally conductive filler.
4. The rubber composition for dynamic sealing according to claim 1, characterized in that, The rubber composition for dynamic sealing meets the following performance indicators: hardness of Shore A 60-75; tensile strength ≥12MPa; elongation at break ≥300%; compression set ≤20% under 150℃×24h conditions.
5. A method for preparing a dynamic sealing rubber composition as described in claim 1, characterized in that, Includes the following steps: Pretreatment: The nano-reinforced filler and a portion of the anti-fatigue agent are stirred and pretreated to obtain a pretreated filler system; First stage of mixing: The hydrogenated nitrile rubber and the polyurethane rubber are plasticized, and then the pretreated filler system, the wear-resistant additive and the composite antioxidant are added and mixed. The glue is discharged to obtain the premixed rubber. Two-stage mixing: After cooling the premixed rubber, the vulcanizing agent, the functional additive and the remaining anti-fatigue agent are added and mixed to obtain the dynamic sealing rubber composition.
6. The method for preparing the dynamic sealing rubber composition according to claim 5, characterized in that, The temperature of the first stage of mixing is controlled at 110-120℃; the temperature of the second stage of mixing is controlled at 80-95℃.
7. The method for preparing the dynamic sealing rubber composition according to claim 6, characterized in that, The plasticizing time is 60-80 seconds; the mixing time after adding the pretreated filler system, the wear-resistant agent and the composite antioxidant in the first stage of mixing is 90-120 seconds; the mixing time of the second stage of mixing is 60-90 seconds.
8. The method for preparing the dynamic sealing rubber composition according to claim 5, characterized in that, In the pretreatment, the nano-reinforced filler and part of the anti-fatigue agent are fully dispersed by high-speed stirring; in the second-stage mixing, the cooled premixed rubber is put back into the internal mixer and mixed after adding the vulcanizing agent, the functional additive and the remaining anti-fatigue agent.
9. A dynamic seal, characterized in that, The material of the dynamic seal comprises the rubber composition for dynamic sealing as described in any one of claims 1 to 4.
10. The application of the dynamic seal as described in claim 9 in the joint sealing of AI humanoid robots.